Analisis Kepuasaan Karyawan Terhadap Penggunaan Website Sistem Kepegawaian sebagai Media Kerja di Sekretariat Kepaniteraan Mahkamah Agung RI Menggunakan Metode EUCS - Muhammad Rafi; Ana Ramadhayanti (Trending: Jurnal Manajemen dan Ekonomi, 2024)
There are many improvements in technological developments that can be done or developed, such as a system or website to make it easier for humans to do their work in completing work. However, with the existence of a website, a study is also needed to measure the satisfaction value of the use of the website itself, one of which is the personnel system website is a personnel system website that gives you convenience in completing work, with this personnel system website now it is easy for humans to do work easily because they can do work online. This study was conducted to determine the level of user satisfaction of the personnel system website where in this study the author uses the End User Computing Satisfaction (EUCS) method, this method emphasizes user satisfaction by analyzing applications based on content, accuracy, format, user convenience and timeliness. The type of research conducted is a type of descriptive research using research instruments in the form of questionnaires. The sampling technique in this study is a random sample. This research is felt to be necessary to find out the level of satisfaction of website users.